PERKEMBANGAN SISTEM PENDETEKSI BANJIR BERBASIS IoT : SYSTEMATIC LITERATURE REVIEW - Muhammad Al Farrabi Bobi (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2023)
This study aims to produce a systematic literature review. The process of writing a Systematic Literature Review (SLR) is carried out according to the framework. With high rainfall during the rainy season it can make it rain continuously and cause an increase in the volume of water that has the potential for flooding. While the community did not receive information or notification directly when this would occur. To anticipate these problems, the design of a water level monitoring system as an IoT-based early flood detector is considered efficient. This paper extracts from various publications regarding IoT-based flood detection systems specifically. This study examines identifying and selecting the methods used in this study, what is the purpose of this research in developing an IoT-based flood detection system, how do we compare the results of the flood detection systems that have been carried out. In this paper we present the results of the development of a flood detection system in each of the previous studies. As a result, the main contribution of this paper is to review research on the development of IoT-based flood detection systems.